2012
DOI: 10.1134/s0869591112020063
|View full text |Cite
|
Sign up to set email alerts
|

Hydrosilicate liquids in the system Na2O-SiO2-H2O with NaF, NaCl and Ta: Evaluation of their role in ore and mineral formation at high T and P

Abstract: Consideration of the existence of hydrosilicate liquids (HSL) in nature can help in understanding the accumulation and transport of some mineral and ore forming components at the transition from mag mas to hydrothermal fluids. We studied the experimental formation of HSL using a base system Na 2 O-SiO 2 -H 2 O with addition of NaF, NaCl and metallic Ta. The interaction between quartz and aqueous solution, per formed at 1.5 kbar and 600°C and followed either by cooling or by quench, showed that the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 35 publications
(34 reference statements)
1
32
0
8
Order By: Relevance
“…In addition, the compositions of the dissolved daughter minerals observed within the CIs indicate that this type of carbonate aqueous fluid is rich in silicate and alkali metals. Its composition appears to be close to that of hydrosilicate liquids with a low viscosity, high element diffusion, and a capacity for mass transport, enabling extreme concentrations of lithophile ore metals [42,43]. These observations provide useful information for evaluating the formation models of the rare-metal pegmatites, such as those suggested by London [15], Thomas et al [19], and Thomas and Davidson [40].…”
Section: Discussionmentioning
confidence: 89%
“…In addition, the compositions of the dissolved daughter minerals observed within the CIs indicate that this type of carbonate aqueous fluid is rich in silicate and alkali metals. Its composition appears to be close to that of hydrosilicate liquids with a low viscosity, high element diffusion, and a capacity for mass transport, enabling extreme concentrations of lithophile ore metals [42,43]. These observations provide useful information for evaluating the formation models of the rare-metal pegmatites, such as those suggested by London [15], Thomas et al [19], and Thomas and Davidson [40].…”
Section: Discussionmentioning
confidence: 89%
“…In such systems the alkalis remain in solution as ions, providing a simple mechanism for the strong separation of the silica gel. For example, Smirnov et al (2012) showed experimentally that a minimum of 2 wt.% Na 2 O was required to produce a colloidal form of silica (a hydrosilicate liquid or HSL in their terminology), and that above that value the amount of HSL formed was proportional to the amount of Na 2 O present. Mustart (1972) demonstrated a possible alternative to meltÀmeltÀfluid immiscibility processes by using a hydrous albite and sodium disilicate melt as a model for peralkaline magmas.…”
Section: Discussion and Interpretationmentioning
confidence: 99%
“…Recently, Smirnov et al (2012) published a study which addressed an intermediate composition, with approximately equimolar H 2 O and SiO 2 . They showed that at Na 2 O concentrations >2 wt.% a water-and a silica-rich phase, referred to as a hydrosilicate liquid (HSL), with colloidal properties, developed from water-and alkali-rich silicate melts at~600ºC and remained relatively stable to low temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term "gel state" is used by the cited authors and especially by Smirnov et al [40] sensu lato for hydrosilicate liquids derived experimentally from the simple system Na 2 O-SiO 2 -H 2 O. In this system with more than 15% (g/g) Na 2 O the formation of gels is plausible, because other glass formers (B 2 O 3 , Al 2 O 3 ) are missing.…”
Section: The Significance Of the Gel State In Pegmatite Evolutionmentioning
confidence: 99%